An analysis of motivating factors at the workplace: the case for hospitality and education industry / Muhammad Haziq Abd. Rashid, Nur Maisarah Mohd. Mukhlizam and Puteri Nur Marissa Mohd. Fauzi - Abd. Rashid, Muhammad Haziq; Mohd. Mukhlizam, Nur Maisarah; Mohd. Fauzi, Puteri Nur Marissa (Universiti Teknologi MARA, 2020)
The study explores the factors influencing motivation of employees in organization. It focuses on two different professional industries; hospitality and education. This study also denotes the importance of certain elements that can help to build the fundamental cores of an organization. There are three main motivational factors that can be considered as important variables in achieving the organization's goals; leadership styles, organizational environment and reward system. In the context of working in a professional setting, achieving the organizational goals is a vital step in sustaining the organization's performance. Motivation at the workplace was seen as one of the crucial elements that help in achieving organizational goals. Hence this study was conducted to analyse the three main motivational factors and how they influence an organization. Furthermore, a theoretical framework was also designed to cater to research requirements. Future studies may apply the theoretical framework designed in this study to explore other areas that are relevant to other factors that can drive organizational members into achieving the goals set.